China's structural transformation: reaching potential GDP in the financial services sector - Sara Hsu; Alba Carolina Melchor Simon (China Finance and Economic Review, 2016)
China's economy faces the daunting challenge of shifting from a manufacturing-based economy to a service-based economy. Reforms in the services sector are slated to continue to take place in the coming years, including in the financial sector. In this paper, we explore China's success and challenges with structural change and then take a closer look at the financial services sector to find out where reforms have occurred, where the potential lies, and what the future will bring. We first describe structural change with regard to growth and TFP (total factor productivity), then as it applies to China. We examine China's financial services sector. Next, we calculate potential GDP of the financial services sector now and with the implementation of expected reforms. We find that, given even conservative estimates, the value added of the financial intermediation sector could double, as labor, capital, technology, and elasticity respondto liberalization policies. Whether potential GDP under reforms is reached is another question; therefore, we recommend that China both increase the pace of implementation, focusing in particular on reducing the oligopoly in the banking sector, increasing investment options by reforming its bond and equity markets, and enhancing innovation in the financial sphere while controlling for risk.
Keywords: 330; China; Financial sector; Structural transformation; Banking